Pengaruh Konsentrasi Karagenan Terhadap Karakteristik Fisikokimia dan Sensoris Permen Jeli Loloh Cem-cem - Diah Ernawati, Ni Komang; Kartika Pratiwi, I Desak Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Jelly candy is a type of soft candy made from fruit or vegetable juice, diversification of jelly candy can use loloh as the main ingredient. Loloh cem-cem has a sweet and sour taste so it is suitable as a raw material for jelly candy, in making jelly candy it is necessary to add gelling agents to form a chewy texture. This study aims to determine the effect of carrageenan concentration on the physicochemical and sensory characteristics of jelly candy and to obtain the most appropriate carrageenan concentration to produce jelly candy with the best physicochemical and sensory characteristics. The design used in this study was a completely randomized design with treatment consisted of 5 levels of carrageenan concentration; 2%, 3%, 4%, 5%, and 6%. Each treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by analysis of variance and continued with Duncan's Multiple Range Test for the treatments that had a significant effect. The results showed that concentration of carrageenan on loloh cem-cem jelly candy had a significant effect on texture, water content, crude fiber, sensory texture and overall acceptance. Concentration of 6% carrageenan produced loloh cem-cem jelly candy with the best characteristics i.e: texture 5.11 N, water content 15.75%, crude fiber 1.23%, antioxidant activity 34.15%, texture very chewy and liked, color, aroma, taste, overall acceptance was liked by the panelists.